2020
DOI: 10.1002/ghg.2044
|View full text |Cite
|
Sign up to set email alerts
|

A study on the impact of storage boundary and caprock morphology on carbon sequestration in saline aquifers

Abstract: Structural trapping is known to be the primary storage mechanism in geological carbon sequestration (GCS), where the injected CO 2 rises upwards due to buoyancy forces and becomes trapped under an ultra-low permeability layer. Although it is relatively common in GCS studies to assume a planar caprock for the synthesised models, in a real scenario this is not always the case as the caprock might exhibit some small-or large-scale topography changes. Moreover, little is known about the impact of the caprock morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 106 publications
(218 reference statements)
0
3
0
Order By: Relevance
“…In Equation (11), G de represents the annual water purification amount of the evaluated forest, and K s represents the water purification cost. In terms of carbon sequestration and oxygen release capacity, the calculation of the carbon sequestration value is shown in Equation ( 12) [36].…”
Section: Construction Of Evaluation Index System For Urban Forest Eco...mentioning
confidence: 99%
“…In Equation (11), G de represents the annual water purification amount of the evaluated forest, and K s represents the water purification cost. In terms of carbon sequestration and oxygen release capacity, the calculation of the carbon sequestration value is shown in Equation ( 12) [36].…”
Section: Construction Of Evaluation Index System For Urban Forest Eco...mentioning
confidence: 99%
“…Ahmadinia and Shariatipour [89,90] found that slight variation of the topography of the interface between the caprock and the upper reservoir, within the aforementioned limits on seismic resolution, led to substantial improvement in the agreement between Darcy flow simulations and the observations of plume distribution.…”
Section: Internal Barriersmentioning
confidence: 99%
“…As a result, the cumulative amount of CO 2 to be stored in the formation decreases, with a larger extent updip and smaller downdip . Ahmadinia found that increasing the dip angle increased the buoyancy of CO 2 , resulting in more space for injected CO 2 to migrate upward, with a larger migration distance and interaction with more formation water. Wang , and Jing , found that formation dip angle had a certain impact on CGS.…”
Section: Introductionmentioning
confidence: 99%